Multi-trait selection of bread wheat ideotypes for adaptation to early sown condition - Farhad, Md.; Shashi Bhushan Tripathi; Singh, Ravi Prakash; Joshi, Arun Kumar; Bhati, Pradeep; Vishwakarma, Manish Kumar; Mondal, Suchismita; Malik, Anoop Anand; Kumar, Uttam (Wiley, 2022)
Genotypes developed for a particular mega environment or management condition may not suit different management or specific local environments. Planting earlier than the recommended planting time is currently a new avenue to improve genotypic performance, supporting horizontal yield increases in the region when winter is shortening. In India, wheat-growers are looking at early planting because it can use residual soil moisture from monsoons and escape terminal heat stress. A BLUP-based multi-environmental stability analysis was conducted on three sets of genotypes across three consecutive years (2017, 2018, and 2019) under early and timely planting dates to identify genotypes for further breeding. A number of traits were studied - phenological (EGC, DTB, DTHD, DAYSMT, BTH, and GFD), plant stature (PH, HUS, and SpkLng), flag leaf (FLGLFL, FLGLFW, and FLGLFA), and yield traits (TGW and GRYLD). A significant genotypic effect was observed for all traits in the single environment analysis. A GEI was observed in the mixed-effect model, except for FLGLFA in season 2 and SpkLng in season 3. Residual components of variation were found to increase under early planting for all studied traits due to exposure of genotypes to early heat and a prolonged growing period. A higher GEI was observed in dissected phenological events such as BTH and GFD. Among phenological traits, it was found that DTB, GFD, and DAYSMT were strongly supporting selection gain throughout all seasons under early planting. The genotypes with a more extended vegetative period and grain filling period were tend to have higher grain yield and TGW under early planting.